Method for improving biogas biological purification efficiency based on nano zero-valent iron composite material
By covering the protective layer on the surface of nano zero-valent iron, the problems of insufficient hydrolysis and low methane production efficiency in traditional anaerobic digestion technology are solved, efficient biopurification of biogas is achieved, and methane content and biogas quality are improved.
Patent Information
- Application Number
- CN202311245135.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-25
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2043-09-25
AI Technical Summary
Traditional anaerobic digestion technology has problems such as insufficient hydrolysis and low methane production efficiency, which leads to low calorific value of biogas and hinders its use as renewable natural gas into the natural gas pipeline network. Existing bio-purification methods such as physical absorption method and chemical absorption method have problems such as high energy consumption, cumbersome operation and high operating costs.
The nano zero-valent iron composite material is prepared by covering the macromolecular protective layer on the surface of nano zero-valent iron (nZVI), reducing the toxic effect of nanoparticles on microorganisms, providing sufficient H2 for hydrophilic methanophilic bacteria, converting CO2 in the system into CH4, thereby improving methane content and biopurification efficiency of biogas.
It improves the content and stability of methane during anaerobic digestion, enhances the gas-liquid mass transfer efficiency of hydrogen, reduces the redox potential, creates a favorable environment for microorganisms, and significantly improves the efficiency of biopurification of biogas.
Smart Images

Figure CN119683768A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for improving biogas biological purification efficiency based on nano zero-valent iron composite materials, belonging to the technical fields of treatment and utilization of organic wastewater and environmental protection energy. Background Art
[0002] Anaerobic digestion can not only solve the ecological and environmental problems caused by wastewater, but also generate energy materials such as biogas to alleviate the current tense contradiction between energy supply and demand. It has the characteristics of low cost and low energy consumption. However, traditional anaerobic digestion technology generally has the problems of insufficient hydrolysis and low methane production efficiency. CO2, as an inert gas present in biogas, will reduce the calorific value of biogas, hindering it from becoming renewable natural gas and being incorporated into the natural gas pipeline network for use. In order to overcome the problem of low calorific value of biogas, purifying biogas is a key measure to improve anaerobic digestion. The use of physical absorption, chemical absorption, pressure swing adsorption and other methods to remove CO2 from the system has the problems of high energy consumption, cumbersome operation and high operating cost. Biogas biological purification can not only reduce CO2 emissions but also improve energy efficiency by directly converting CO2 into usable energy in the anaerobic system.
[0003] When CO2 is reduced by H2 and used for hydrogenation reaction, methane is produced. It has the advantages of low operating cost, mild reaction conditions and environmental friendliness. Due to the low gas-liquid mass transfer rate of H2, the utilization of H2 by methanogens is limited. Nano-zero-valent iron (nZVI) can provide hydrogen in situ inside the anaerobic system by corroding and releasing hydrogen through reaction with water, making full use of hydrogenophilic methanogens to convert H2 and CO2 into CH4. Nano-zero-valent iron can provide a hydrogen source for microorganisms through corrosion and hydrogen release, reduce the redox potential (ORP) to create a favorable environment for microorganisms, stimulate key enzymes to promote the hydrolysis and acidification process, and strengthen interspecies direct electron transfer (DIET) to change the community structure of dominant bacteria in anaerobic digesters, thereby increasing methane production. However, due to the characteristics of nZVI agglomeration and passivation, its hydrogen release performance is lower than the theoretical value. On the other hand, due to the low utilization rate of H2 and CO2 by hydrogenophilic methanogens, the contribution of nano-zero-valent iron to anaerobic digestion and methane production is still low, thus limiting the efficiency of biogas biopurification. Summary of the invention
[0004] In view of the problems existing in the prior art, the present invention provides a method for improving the efficiency of biogas biological purification based on nano zero-valent iron composite materials. A macromolecular protective layer is physically covered on the surface of nZVI to prepare a nano zero-valent iron composite material. The use of the nano zero-valent iron composite material can reduce the toxic effect of nanoparticles on microorganisms, provide sufficient H2 for hydrogenophilic methanogens, convert CO2 in the system into CH4, reduce the CO2 content in the system, increase the methane content, and thereby improve the efficiency of biogas biological purification.
[0005] In view of the above-mentioned purpose, the present invention provides a method for improving the efficiency of biogas biological purification based on nano zero-valent iron composite materials, comprising the following steps: adding the nano zero-valent iron composite material to kitchen wastewater, adding anaerobic granular sludge to the mixed system, maintaining the pH of the entire reaction system at 7.2±0.2, blowing with nitrogen for 5 minutes to maintain an anaerobic environment, and collecting the generated biogas using a gas collection bag; wherein the nano zero-valent iron composite material includes nano zero-valent iron coated with extracellular polymers and / or nano zero-valent iron coated with sodium dodecyl sulfate.
[0006] In one embodiment of the present invention, in a mixed system of the nano zero-valent iron composite material and kitchen wastewater, the concentration of the nano zero-valent iron composite material is 10 g / L.
[0007] In one embodiment of the present invention, the concentration of SCOD in the food wastewater is 13066±123 mg / L, and the food wastewater and anaerobic granular sludge are inoculated at an inoculation ratio of 1 to 1.5:1 (COD:VSS).
[0008] In one embodiment of the present invention, a buffer is used to adjust the pH of the entire reaction system, and the buffer is NaHCO3.
[0009] In one embodiment of the present invention, the reaction temperature of the entire reaction system is 35-37°C.
[0010] In one embodiment of the present invention, the preparation method of the nano zero-valent iron composite material comprises the following steps: adding nano zero-valent iron to a polymer precursor solution to obtain a dispersion, adjusting the pH of the dispersion to 7.0±0.2, and removing the air in the system by nitrogen blowing, stirring under anaerobic conditions, and separating the obtained solid to obtain a nano zero-valent iron composite material.
[0011] In one embodiment of the present invention, the polymer precursor is extracellular polymer and / or sodium dodecyl sulfate, and the concentration of the polymer precursor solution is 6-14 mg / L.
[0012] In one embodiment of the present invention, the concentration of the polymer precursor solution is 10-12 mg / L.
[0013] In one embodiment of the present invention, when the polymer precursor is an extracellular polymer, the concentration of the polymer precursor solution is 10 mg / L.
[0014] In one embodiment of the present invention, when the polymer precursor is sodium dodecyl sulfate, the concentration of the polymer precursor solution is 12 mg / L.
[0015] In one embodiment of the present invention, the concentration of nano zero-valent iron in the dispersion is 10 g / L.
[0016] In one embodiment of the present invention, the stirring includes mechanical stirring, the stirring speed is 200-400 rpm, and the stirring time is 30 minutes, so that the polymer is wrapped on the surface of the nano zero-valent iron to form a nano zero-valent iron composite material. The polymer is wrapped on the surface of the nano zero-valent iron in the form of microparticles, thereby forming a slow-release protective layer.
[0017] The present invention also provides a nano zero-valent iron composite material prepared according to the above preparation method.
[0018] The present invention also provides an application of the nano zero-valent iron composite material in the field of biogas biological purification.
[0019] Beneficial Effects of the Invention
[0020] (1) The present invention uses kitchen wastewater as a substrate and adopts nano zero-valent composite materials (EPS 10 -nZVI 10 、SDS 12 -nZVI 10 ) In-situ corrosion hydrogen supply to improve biogas quality. The addition of nano zero-valent iron composite materials increased the content and stability of methane (CH4) during anaerobic digestion. 10 -nZVI 10 、SDS 12 -nZVI 10 With the addition of , the CH4 content increased, reaching a maximum of 93.33%, which was 22.83% higher than the control group without addition. After adding the nano zero-valent iron composite material, the maximum hydrogen enrichment (HE) was 561ppb, indicating that the mass transfer efficiency of hydrogen was improved. Due to the addition of the nano zero-valent composite material, the ORP dropped from -101 to -190mV to -108 to -298mV, providing a more favorable environment for anaerobic fermentation.
[0021] (2) The material of the present invention is simple to synthesize. By changing the agglomeration and passivation characteristics of nZVI, its corrosion hydrogen evolution performance is further improved, providing a hydrogen source for the biological methanogenesis process. The biological purification of biogas converts kitchen wastewater into high-purity methane products, realizing the treatment of organic wastewater and the acquisition of renewable energy. The present invention has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 is a schematic diagram of the reaction device;
[0023] Figure 2 The corrosion and hydrogen evolution of nano-zero-valent iron coated with extracellular polymers of different concentrations in aqueous solution;
[0024] Figure 3 The corrosion and hydrogen evolution of nano zero-valent iron coated with sodium dodecyl sulfate at different concentrations in aqueous solution;
[0025] Figure 4 The proportion of gas components in food wastewater with different materials added: (a) CH4; (b) CO2; (c) H2;
[0026] Figure 5 Cumulative gas production changes of kitchen wastewater with different materials added: (a) Cumulative gas production and BMP changes; (b) Cumulative methane and biogas production;
[0027] Figure 6 The changes of pH, HE and ORP of kitchen wastewater with the addition of different materials: (a) pH; (b) HE; (c) ORP;
[0028] Figure 7 The changes of SCOD and VFA yields in food wastewater with the addition of different materials: (a) SCOD; (b) VFA;
[0029] Figure 8 Enzyme activities of food wastewater with different materials added: (a) acidogenic enzyme; (b) methanogenic enzyme;
[0030] Fig. 9 TEM images of microbial flora in food wastewater with different materials added: (a) CK; (b) EPS 10 -nZVI 10 ; (c) SDS 12 -nZVI 10 ;(A)nZVI;(B)EPS;(C)SDS;
[0031] Fig.10 The changes in the diversity of microbial flora in food wastewater with the addition of different materials: (left) bacterial phylum level; (right) archaea level. Specific implementation method:
[0032] Example 1 Improving the efficiency of biogas biopurification using extracellular polymer (EPS)-coated nano-zero-valent iron
[0033] 1. Determination of the optimal amount of extracellular polymers in nano zero-valent iron composites (EPS-nZVI)
[0034] Prepare 400 mL of extracellular polymer (EPS) solution in a reaction bottle, adjust the pH of the solution to 7.0±0.2, and introduce nitrogen for 5 minutes to keep the reaction device in an anaerobic environment; evenly disperse the nano zero-valent iron in the extracellular polymer solution so that the concentration of nano zero-valent iron in the dispersion is 10 g / L, mechanically stir the dispersion under anaerobic conditions to obtain a nano zero-valent iron composite material, and use a gas collection bag to collect the generated hydrogen. The stirring speed is 200-400 rpm and the stirring time is 30 minutes.
[0035] Extracellular polymer solutions with concentrations of 6 mg / L, 8 mg / L, 10 mg / L, 12 mg / L, and 14 mg / L were prepared respectively, and the production of hydrogen during the corrosion and hydrogen evolution of nano-zero-valent iron coated with extracellular polymers of different concentrations was tested using the drainage method. The results are as follows: Figure 2 As shown, from Figure 2 It can be seen that when the concentration of extracellular polymers is 10 mg / L, the hydrogen production is the highest.
[0036] 2. Improving the efficiency of biogas biopurification by using nano-zero-valent iron coated with extracellular polymers (EPS)
[0037] The nano zero-valent iron composite material (EPS) prepared in step 1 10 -nZVI 10 ) was added to 400 mL of kitchen wastewater diluted 6 times (SCOD = 13066 ± 123 mg / L), so that the concentration of nano zero-valent iron composite material was 10g / L, and the COD in the wastewater was 13066.7 mg / L. Anaerobic granular sludge was inoculated into the mixed system at an inoculation ratio of 1.2: 1 (COD: VSS), NaHCO3 was used as a buffer, pH was controlled at 7.2 ± 0.2, the reaction temperature was 35-37 ° C, and nitrogen was blown off for 5 minutes to maintain an anaerobic environment. Biogas was collected using a gas collection bag.
[0038] The gas composition and content were determined by gas chromatography; VFAs, SCOD, dehydrogenase activity, alkaline protease activity, acetate kinase activity, F 420 The activity and TEM images of microorganisms and their diversity were measured; the measurement methods were analyzed using national standard methods, and the specific test methods are shown in Table 1.
[0039] Table 1 Test methods for various parameters
[0040]
[0041] Example 2 Improving the efficiency of biogas biopurification using sodium dodecyl sulfate (SDS)-coated nano zero-valent iron
[0042] The difference between Example 2 and Example 1 is that in step 1, the extracellular polymer (EPS) in Example 1 is replaced with sodium dodecyl sulfate (SDS), and sodium dodecyl sulfate solutions with concentrations of 6 mg / L, 8 mg / L, 10 mg / L, 12 mg / L, and 14 mg / L are prepared respectively. The drainage method is used to test the hydrogen production during the corrosion and hydrogen evolution process of nano zero-valent iron coated with sodium dodecyl sulfate at different concentrations. The results are as follows Figure 3 As shown, from Figure 3 It can be seen that when the concentration of extracellular polymers is 12 mg / L, the production of hydrogen is the highest, so it can be determined that the optimal concentration of sodium dodecyl sulfate (SDS) is 12 mg / L.
[0043] Comparative Example 1 Biogas Biopurification Using Nano Zero-Valent Iron
[0044] The difference between Comparative Example 1 and Example 1 is that step 1 is omitted, and the nano zero-valent iron composite material in step 2 is replaced by nano zero-valent iron.
[0045] Comparative Example 2 Biogas Biopurification Using EPS
[0046] The difference between Comparative Example 2 and Example 1 is that step 1 is omitted, and the nano zero-valent iron composite material in step 2 is EPS 10 -nZVI 10 .
[0047] Comparative Example 3 Biogas Biopurification Using SDS
[0048] The difference between Comparative Example 3 and Example 1 is that step 1 is omitted and the nano zero-valent iron composite material in step 2 is SDS 12 -nZVI 10 .
[0049] Comparative Example 4 Blank Control (CK)
[0050] The difference between Comparative Example 4 and Example 1 is that step 1 is omitted, and step 2 is a system containing only food wastewater and anaerobic granular sludge.
[0051] Experimental Results
[0052] (1) Proportion of gas components in food wastewater with different materials added
[0053] The biogas biopurification conditions and the in-situ hydrogen supply conditions of various materials in the anaerobic system in Examples 1 to 2 and Comparative Examples 1 to 4 are as follows: Figure 4 The experimental results show that the nano zero-valent iron composite materials in Examples 1 and 2 have a significant improvement in the efficiency of biogas purification, and the methane content in Examples 1 and 2 can reach 92.56% and 93.37% respectively ( Figure 4 (a)). Figure 4 It can be seen that in the anaerobic system, hydrogenophilic methanogens use H2 to convert CO2 in the anaerobic system into CH4, which is consistent with the trend of gradually increasing CH4 content and gradually decreasing CO2 and H2 content. Compared with Examples 1 and 2 in which nano zero-valent iron composite materials are added, the CO2 residual amount in the comparative example is higher and the H2 content is lower, indicating that the nano zero-valent iron composite material increases the H2 production and the utilization rate of CO2 and H2, which is beneficial to biogas biopurification in the anaerobic system. The composite material formed by EPS and SDS can reduce the passivation of the nZVI surface, thereby releasing more active centers and increasing the hydrogen supply of the system. In addition, the Fe released by the composite material 2+ It can promote the enrichment of methane to a certain extent, which is more conducive to the growth of microorganisms. The experimental results show that the two nano zero-valent iron composite materials in the embodiment can increase the content of CH4 in biogas, and compared with the uncoated nano zero-valent iron, the two nano zero-valent iron composite materials have a higher methane content in the anaerobic system, indicating that the composite materials can increase the gas-liquid mass transfer rate and utilization rate of H2 in biogas.
[0054] (2) Changes in the cumulative gas production of food wastewater with the addition of different materials
[0055] The effects of Examples 1 to 2 and Comparative Examples 1 to 4 on the cumulative gas production in the anaerobic system are as follows: Figure 5 The experimental results show that EPS 10 -nZVI 10 、SDS 12 -nZVI 10 The addition of Figure 5 (a)), reaching 506.93ml / gVS and 510.96ml / gVS, respectively, which are 20.98% and 21.94% higher than those of comparative example 4 (CK). The nano zero-valent iron composites wrapped with EPS and SDS not only increase the biogas production, but also have a relatively high proportion of methane. Compared with comparative example 4 (CK), the methane content can be increased by 57.89% and 56.04% ( Figure 5 (b)). The BMP value is used to evaluate the degradation rate of organic matter during anaerobic digestion. The larger the BMP, the higher the degradation rate. By calculating the biomethane potential, it can be obtained that EPS 10 -nZVI 10 、SDS 12 -nZVI 10 The addition of can make the BMP value reach 99% ( Figure 5 (a)), it is believed that these two composite materials can significantly improve the efficiency of anaerobic digestion and enhance the production of methane. It is further shown that the two nano zero-valent iron composite materials can increase the content of CH4 in biogas, which is conducive to the biological purification of biogas in the anaerobic system.
[0056] (3) Changes in pH, HE, and ORP of food wastewater after adding different materials
[0057] The effects of the changes in pH, HE and ORP in the anaerobic system in Examples 1 to 2 and Comparative Examples 1 to 4 are as follows: Figure 6 The change of pH in the anaerobic system can affect the activity of anaerobic bacteria. Compared with Comparative Example 4 (CK), the change of pH after adding the nano zero-valent iron composite materials of Examples 1 and 2 is smaller ( Figure 6 (a) This may be due to the generation of OH during the hydrogen release process of nano-zero-valent iron. - . At the end of anaerobic digestion of kitchen wastewater, the maximum pH of the reaction system was 8.13 (nZVI), which can be maintained within the optimal activity range of anaerobic digestion bacteria. The hydrogen enrichment value (HE) reflects the hydrogen content in the liquid phase. The in-situ hydrogen evolution effect of the nano zero-valent iron composite material can increase the hydrogen content in the liquid phase, that is, the hydrogen enrichment value (HE) increases. The hydrogen enrichment values all reached their maximum on the second day of the reaction. The hydrogen enrichment values in Examples 1 to 2 and Comparative Examples 1 to 4 were 550, 561, 540, 259, 266, 531, 279, and 278 ppb, respectively. Figure 6 (b)). The study found that within 2 to 6 days, the gradual consumption of H2 was consistent with the increasing trend of CH4 content in biogas, which indicates that the improvement of biogas biopurification efficiency promotes the generation of CH4. ORP can affect the fermentation type of anaerobic digestion system. Relatively low ORP is conducive to the occurrence of hydrogenotrophic biomethanization ( Figure 6 (c)). The addition of the nano zero-valent iron composite materials of Examples 1 and 2 resulted in a significant decrease in ORP, with the largest ORP changes of 0 to -285 and 0 to -295, respectively. The rapid decrease in ORP can promote the conversion of propionic acid to acetic acid and can effectively increase the activity of dehydrogenase. The decrease in ORP may be one of the reasons for the increase in CH4 production after the addition of the nano zero-valent iron composite materials.
[0058] (4) Changes in SCOD and VFA of food wastewater after adding different materials
[0059] In the process of anaerobic fermentation of food wastewater to produce VFA, VFA / SCOD can indicate the degree of conversion of dissolved organic matrix into VFA and is an important indicator for measuring acidification efficiency. Figure 7 As shown in the figure, in the anaerobic digestion treatment of kitchen wastewater, most of the SCOD is easily degraded by anaerobic microorganisms, and the SCOD concentration gradually decreases. Within the first day, SCOD dropped from the initial concentration of 11920 mg / L to about 5900 mg / L, and the degradation rate reached about 50%. After 6 days of anaerobic digestion, the SCOD concentration in the final reaction system was less than 200 mg / L ( Figure 7 (a)). Figure 7As can be seen in (a), after adding the nano zero-valent iron composite materials of Examples 1 and 2, the initial concentration of COD decreased faster within the first day, indicating that adding the nano zero-valent iron composite materials is beneficial to reducing the COD in kitchen wastewater.
[0060] The concentration of VFAs in food wastewater first increased and then decreased ( Figure 7 (b)) Within the first day, the VFAs concentration increased from the initial 0.88-0.90 g / L to 1.42-1.80 g / L, and the VFAs concentration reached the maximum value on the first day. Among them, the CK group had the highest concentration of 1.809 g / L, and then gradually decreased. This shows that under this condition, the organic matter was fully decomposed and the CH4 production increased. Figure 7 From the influence curve of each material on the VFAs concentration in (b), it can be seen that after adding the nano zero-valent iron composite materials in Examples 1 and 2, the concentration of VFAs in the kitchen wastewater increases slowly within 1 day, and the concentration of VFAs decreases rapidly with the extension of time, indicating that the addition of nano zero-valent iron composite materials is beneficial to improving the efficiency of organic matter decomposition and further increasing the production of CH4.
[0061] (5) Enzyme activity of food wastewater with different materials added
[0062] In the anaerobic fermentation of kitchen wastewater to produce methane, a variety of enzymes are involved, such as α-glucosidase, acetate kinase (ACK), F420, etc. Figure 8 The key enzyme activities of the sludge in each system after the reaction is completed. α-Glucosidase can release glucose from oligosaccharide substrates; alkaline protease can promote the hydrolysis of protein in organic matter; acetate kinase is the key enzyme for the production of acetic acid. Among them, the enzyme activities in Examples 1 and 2 are significantly improved compared with those in Comparative Example 4 (CK), and the enzyme activities in Examples 1 and 2 are also improved compared with those in Comparative Example 1 (system with nano zero-valent iron added), which indicates that the addition of nano zero-valent iron composite materials increases the activity of related enzymes and promotes the hydrolysis and fermentation of kitchen wastewater by microorganisms ( Figure 8 (a)). Dehydrogenase and coenzyme F 420 It is an important enzyme activity in the biological methanogenesis process. Dehydrogenase is involved in the conversion of H2 and CO2 to CH4. The activity of dehydrogenase in Example 1 and Example 2 was 5.95 and 5.90 μg / min / gVS, respectively, which was 431.25% and 423.79% higher than that in Comparative Example 4 (CK). Moreover, since the nano zero-valent iron composite material can provide a lower ORP, the dehydrogenase can maintain a higher activity under this condition, which is beneficial for microorganisms to efficiently utilize H2 and CO2, thereby increasing the methane yield. Coenzyme F 420 It is a methanogenic enzyme that is mainly involved in the production of CH4. In Examples 1 and 2, coenzyme F 420The activity was increased by 224% and 228% respectively compared with the CK group (Comparative Example 4). The results showed that EPS 10 -nZVI 10 、SDS 12 -nZVI 10 The addition of coenzyme F 420 In addition, the Fe 2+ It can also improve the activity of related enzymes in the biogas purification system, which has a promoting effect on improving the CO2 conversion rate. 420 The higher activity indicates that the hydrogenotrophic methanogenesis activity in the biogas purification system is higher, which improves the conversion efficiency of H2 and CO2 to CH4.
[0063] (6) TEM images of microbial flora in food wastewater with different materials added
[0064] The integrity of the cells can be observed from the TEM images of the microorganisms, indicating that the added nano-zero-valent iron composite material did not damage the cells. Compared with the nano-zero-valent iron that is evenly wrapped around the cells, the nano-zero-valent iron composite material surrounds the cells, which can reduce the toxic effect of nanoparticles on microorganisms to a certain extent. Fig. 9 The EPS content around the microbial cells in (b) is significantly higher than that in other groups. The additional EPS can not only coat the nanomaterials, but also serve as a protective layer for microorganisms to prevent nZVI particles from damaging the microbial cell membrane. SDS, as a foaming agent, can prevent nanoparticles from aggregating and adsorbing on the surface of microorganisms and maintain cell viability. This shows that at a certain dose, the coating material can prevent nano-zero-valent iron from damaging microbial cells, thereby enhancing the CH4 generation capacity. In the comparison group with nano-zero-valent iron, EPS decreased slightly ( Fig. 9 (A) This may be due to the small particle size of nZVI particles, which adsorb on the EPS or microbial cell surface, thereby promoting the degradation of EPS. Another possible reason for the slight decrease in EPS is that after contacting with nZVI, the microorganisms adapt to the environment with nZVI particles and gradually reduce the secretion of EPS.
[0065] (7) Changes in the diversity of microbial flora in food wastewater after adding different materials
[0066] Changes in microbial flora diversity under different material additions Fig.10 As shown, Fig.10(Left) shows the relative abundance of bacteria in the system at the phylum level. After anaerobic digestion of food wastewater, the dominant bacteria in all embodiments and comparative examples are mainly composed of Chloroflexi, Bacteroidetes, Firmicutes, etc., accounting for 62% to 69% of the total relative abundance. Chloroflexi can promote the decomposition of sugars in wastewater and produce acetic acid, which is beneficial to anaerobic digestion; Bacteroidetes can convert organic matter into acetic acid and play an important role in the hydrolysis and acidification stages. Firmicutes can effectively degrade macromolecular substrates such as proteins and lipids, and provide substrates for methanogens to produce CH4. The relative abundance of Actinobacteria has decreased, which is beneficial to reduce the accumulation of propionic acid and provide a stable anaerobic digestion environment.
[0067] Fig.10 (Right) shows the relative abundance of the archaeal community at the genus level. The dominant genera in all examples and comparative examples are Methanomassiliicoccus, Methanothrix, Methanobacterium, etc. These dominant archaeal genera have different methane production pathways. Adding EPS 10 -nZVI 10 、SDS 12 -nZVI 10 After that, the relative abundance of Methanomassiliicoccus increased. The relative abundance of Methanothrix increased by 9.61% to 22.22% compared with Comparative Example 4 (CK), because the nano zero-valent iron composite material can improve the utilization of substrates by acid-producing bacteria and promote the conversion of propionic acid to acetic acid. In this process, Methanothrix converts the increased acetic acid in the system as a substrate into CH4. Compared with the control group, Methanobacterium and Methanolinea are hydrogenotrophic methanogens, and their relative abundance increased after adding nano zero-valent iron composite materials. Hydrogenophilic methanogens can convert H2 and keep the hydrogen partial pressure at a low level, increasing CH4 production.
[0068] Although the present invention has been disclosed as above in the form of a preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.
Claims
1. A method for improving biogas biological purification efficiency based on nano zero-valent iron composite materials, characterized in that: The following steps are involved: The nano zero-valent iron composite material is added to the kitchen wastewater, and anaerobic granular sludge is added to the mixed system, the pH of the entire reaction system is maintained at 7.2±0.2, and nitrogen is blown off for 5 minutes to maintain the anaerobic environment, and the generated biogas is collected by a gas collection bag. Among them, the nano zero-valent iron composite material includes nano zero-valent iron coated with extracellular polymers and / or nano zero-valent iron coated with sodium dodecyl sulfate.
2. The method according to claim 1, characterized in that In the mixed system of nano zero-valent iron composite material and kitchen wastewater, the concentration of nano zero-valent iron composite material is 10g / L.
3. The method according to claim 1, characterized in that: The concentration of SCOD in the food wastewater is 13066±123 mg / L, and the food wastewater and the anaerobic granular sludge are inoculated at an inoculation ratio of 1 to 1.5:
1.
4. The method according to claim 1, characterized in that: The preparation method of the nano zero-valent iron composite material comprises the following steps: adding nano zero-valent iron to a polymer precursor solution to obtain a dispersion, adjusting the pH of the dispersion to 7.0±0.2, removing air in the system by nitrogen blowing, stirring under anaerobic conditions, and separating the obtained solid to obtain the nano zero-valent iron composite material.
5. The method according to claim 4, characterized in that The polymer precursor is extracellular polymer and / or sodium dodecyl sulfate, and the concentration of the polymer precursor solution is 6-14 mg / L.
6. The method according to claim 5, characterized in that When the polymer precursor is an extracellular polymer, the concentration of the polymer precursor solution is 10 mg / L.
7. The method according to claim 5, characterized in that When the polymer precursor is sodium dodecyl sulfate, the concentration of the polymer precursor solution is 12 mg / L.
8. The method according to claim 4, characterized in that The concentration of the nano zero-valent iron in the dispersion is 10 g / L.
9. The nano zero-valent iron composite material prepared according to the preparation method according to any one of claims 4 to 8.
10. Application of the nano zero-valent iron composite material according to claim 9 in the field of biogas biological purification.
Citation Information
Patent Citations
Modified nanoscale zero-valent iron and preparing method thereof
CN104226987A
Method for repairing heavy metal contaminated soil by modified nanoscale zero-valent iron synergizing with microorganisms
CN108723073A
Method for strengthening synergistic anaerobic digestion of excess sludge and landfill leachate by zero-valent iron
CN113060918A
Preparation method of sludge extracellular polymeric substance composite nano zero-valent iron
CN113929195A
Method for increasing methane yield in sludge anaerobic digestion process by using nano zero-valent iron
CN115583773A
Cited By
Method for synthesizing short-chain fatty acid by reducing CO2 through zero-valent nano-iron-mediated microorganisms
CN121496017A